Face reading the emotions of gelotophobes toward disparaging humorous advertising - Voutsa, Maria C.; Hatzithomas, Leonidas; Tsichla, Eirini; Boutsouki, Christina (My University, 2022)
Prior research has indicated that gelotophobia, people’s fear of being laughed at, influences their emotions toward a disparaging humorous event. Based on two experiments with a sample of 50 Greek participants each, the present study employed face recognition software to explore the emotions of gelotophobes, when exposed to an advertisement. It further examined the moderating role of the type of advertisement (i.e. a disparaging humorous ad vs. a non-disparaging non-humorous ad) and identification with the victim of the joke, on gelotophobes' emotions. At higher levels of identification with the victim, gelotophobes indicated lower levels of joy, joyful (Duchenne) smile, and a positive emotional valence toward a disparaging-humorous advertisement as opposed to non-gelotophobes. Joy was also found to mediate the negative effects of gelotophobia on attitude toward the ad.
Keywords: Gelotophobia; Disparagement humor; Emotions; Facial expressions recognition